Strukturální změny štěpu z hamstringu způsobené fixačním materiálem a jejich vliv na biomechanické vlastnosti náhrady LCA - Kautzner, Jakub; Držík, Milan; Handl, Milan; Povýšil, Ctibor; Kos, Petr; Trč, Tomáš; Havlas, Vojtěch (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF THE STUDY Hamstring grafts are commonly used for ACL reconstruction. The purpose of our study is to determine the effects of the suspension fixation compared to graft cross-pinning transfixation, and the effect(s) of structural damage during the preparation of the graft on biomechanical properties of the graft. MATERIAL AND METHODS The design of the study is a cadaveric biomechanical laboratory study. 38 fresh-frozen human hamstring specimens from 19 cadaveric donors were used. The grafts were tested for their loading properties. One half of each specimen was suspended over a 3.3mm pin, the other half was cross-pinned by a 3.3mm pin to simulate the graft cross-pinning technique. Single impact testing was performed and the failure force, elongation and acceleration/deceleration of each graft was recorded and the loading force vs. elongation of the graft specimens was calculated. Results for suspended and cross-pinned grafts were analysed using ANOVA method, comparing the grafts from each donor. RESULTS The ultimate strength of a double-strand gracilis graft was 1287 ± 134 N when suspended over a pin, the strength of a cross-pinned graft was 833 ± 111 N. For double-strand semitendinosus grafts the strengths were 1883 ± 198 and 997 ± 234 N, respectively. Thus, the failure load for the cross-pinning method is only 64.7% or 52.9% for the suspension method. DISCUSSION Structural damage to the graft significantly reduces the graft strength. Also, extensive suturing during preparation of the graft reduces its strength. CONCLUSIONS Fixation methods that do not interfere with the graft's structure should be used to reduce the risk of graft failure. Key words: ACL reconstruction, hamstring graft, biomechanical testing.